2006
DOI: 10.1021/ac051990f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D Mapping of Fluidic Temperatures within Microchannel Networks Using Fluorescence Lifetime Imaging

Abstract: We describe a novel method for quantitatively mapping fluidic temperature with high spatial resolution within microchannels using fluorescence lifetime imaging in an optically sectioning microscope. Unlike intensity-based measurements, this approach is independent of experimental parameters, such as dye concentration and excitation/detection efficiency, thereby facilitating quantitative temperature mapping. Micrometer spatial resolution of 3D temperature distributions is readily achieved with an optical sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 43 publications
1
104
0
Order By: Relevance
“…The use of FLIM of RhB to measure the temperature of methanol in micro-fluidic channels has been reported previously (Benninger et al 2006) but the low solubility of RhB in water makes it unsuitable for measuring aqueous systems. We have found that Kiton Red (KR), a water-soluble, sulfonated derivative of RhB, shows the same temperature response as the parent fluorophore and is thus ideal for temperature measurement of aqueous solutions.…”
Section: Measurement Of Temperaturementioning
confidence: 99%
“…The use of FLIM of RhB to measure the temperature of methanol in micro-fluidic channels has been reported previously (Benninger et al 2006) but the low solubility of RhB in water makes it unsuitable for measuring aqueous systems. We have found that Kiton Red (KR), a water-soluble, sulfonated derivative of RhB, shows the same temperature response as the parent fluorophore and is thus ideal for temperature measurement of aqueous solutions.…”
Section: Measurement Of Temperaturementioning
confidence: 99%
“…The lifetime-based techniques generally require more complex diagnostic equipment compared to intensity-based measurements, though they are less sensitive to environmental effects. Besides the temperature measurements, the fluorescent techniques also were employed in studies of flows inside micro channels in lab-on-chip applications [9,10], in microviscosity investigations [11,12], air flow sensing [13,14], and as pressure measurements [15]. In order to achieve stable and reliable results, the certain balance between isolation and overlap of the probe with the environment is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence lifetime imaging (FLIM) [8][9][10] is an increasingly utilized tool in biological research that can provide robust contrast between different fluorescent proteins/species and can also yield quantitative information concerning the local fluorophore environment, e.g. pH, temperature, refractive index [11][12][13], etc., including protein-protein interactions via Fö rster Resonance Energy Transfer (FRET) [14,15]. In this paper we describe a FLIM-OPT system which can reconstruct the 3-D fluorescence lifetime distribution of volumetric samples up to several mm in size, and report its application to imaging mouse embryos.…”
Section: Biophotonicsmentioning
confidence: 99%